Gagasan Kebijakan Hukum Pidana Perluasan Makna Zina Pada Pasal 284 Kitab Undang-Undang Hukum Pidana Dikaitkan dengan Putusan Mahkamah Konstitusi Nomor: 46/PUU-XIV/2016 - Sakti, Usman Bima; Indra, Mexsasai; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The Criminal Code Draft Team made efforts to renew the adultery offense, which is about theadulterers who originally were married men and married women as regulated in positive law in the 2017Criminal Code Draft Article 484 includes men and women who are not bound by each legal marriage withother people. In addition to causing pro-contra, this is exacerbated by the protracted discussion of theCriminal Procedure Code that there are no signs that will be ratified since 1963 until an idea emerges toexpand the meaning of zina through the Constitutional Court but it is rejected by the Constitutional Court.The impact of this adultery can damage the moral and religious values that exist in Indonesian society basedon the supreme divinity, so that gradually this action seems to be a legalized act because of the lack of rulesLaw in Indonesian positive law is a threat to national identity.This type of research used in legal research is a normative juridical method, this research isdescriptive, that is a study that aims to describe the problem clearly and in detail. The source of the dataused secondary data and tertiary legal materials. Data collection techniques in this study with the literaturereview method after the data collected is then analyzed to draw conclusions.From the results of the research and discussion, it can be concluded that, First, the reasons derivedfrom the foundation of moral values / national agreements which state that zina violates the values ofmorality (national agreement) that exist in Pancasila which contain values based on national life for theOne Godhead (religious moral values). Second, the regulation of adultery in the Criminal Procedure Codetends to be overcriminalized and does not pay attention to the impacts that can occur. Third; In order toavoid the implications of legal chaos, the regulation regarding zina should not over criminalize or exposethe principle of ultimum remedium and to overcome the protracted drafting of the RKUHP, the progressivelegal breakthrough is needed by the Constitutional Court to expand the meaning of zina in Article 284 of theCriminal Code In the Constitutional Court Decision Number: 46 / PUU-XIV / 2016 the majority of judgesstill use the legal positivist thinking pattern, which results in the rejection of the material test suit. the strongflow of public opinion that wants the Constitutional Court to be a way out of the deadlock that occursbecause the thing being tested is contrary to moral values.Keywords: Criminal Law Policy - Adultery - Judge's Decision